2005
DOI: 10.1002/biof.5520240106
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase‐induced lipid peroxidation of LDL in the presence of nitrite. Protection by cocoa flavanols

Abstract: Lipid peroxidation (LPO) of low-density lipoprotein (LDL) is believed to be a pivotal process rendering this plasma lipoprotein atherogenic. Several endogenous factors have been proposed to mediate LPO of LDL, among them myeloperoxidase (MPO), which is active in atherosclerotic lesions, and the plasma level of which has been proposed to be a prognostic parameter for cardiac events. Nitrite, a major oxidation product of nitric oxide, is substrate of MPO and a cofactor of MPO-mediated LPO under physiological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…MPO and oxLDL are molecules involved in the development of oxidative stress and consequently in atherosclerosis (22)(23). Particles of oxLDL are generated during lipid peroxidation, and are able to damage endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MPO and oxLDL are molecules involved in the development of oxidative stress and consequently in atherosclerosis (22)(23). Particles of oxLDL are generated during lipid peroxidation, and are able to damage endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that (2 )-epicatechin and other flavonoids protect LDL against oxidation by either MPO/H 2 O 2 /nitrite reaction system or Cu 2 þ catalysis [23,27,28]. Moreover, (2 )-epicatechin protects endothelial cells against both cytotoxicity of oxLDL and oxLDL-mediated proteasomal degradation of endothelial z NO synthase protein [29].…”
Section: Myeloperoxidase-mediated Modifications Of Ldlmentioning
confidence: 92%
“…In a recent review, we have treated the enzymatic properties of myeloperoxidase (MPO) with emphasis on its reactions with nitrite, flavonoids and LDL and their putative biological role in atherogenesis [23]. Main focus of present review is recent work from this laboratory on the cytotoxic action of oxLDL, generated by the MPO/H 2 O 2 /nitrite reaction system, on vascular endothelial cells and its possible role in endothelial dysfunction as well as protective actions of various vasoprotective agents.…”
Section: Introductionmentioning
confidence: 99%
“…In the inflamed subendothelial space, myeloperoxidase is released from activated neutrophils and is capable of inducing lipid peroxidation of low-density lipoprotein at moderate nitrite concentrations (5-50 mM), which may be an initial step in atherogenesis (for a review, see Schewe and Sies, 2005 …”
Section: Nitrite As a Potential Source Of Detrimental Reactive Nitrogmentioning
confidence: 99%